PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIA SD NEGERI 110 PEKANBARU - Novia Andriani; Hendri Marhadi; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted because of the low learning result of IPS students of grade IIIA SDN 110 Pekanbaru, KKM determined at school, that is 75. From 26 students, reaching KKM is only 12 students (46.15%), while students who have not reached KKM is 14 students (53,84%) with grade average grade 62,38. To overcome these problems then the researchers apply the model of learning Role Playing. The purpose of this study is to improve the learning outcomes of IPS students class IIIA SDN 110 Pekanbaru with the application of learning model Role Playing. The results obtained by the average score of the basic score of 62.38 increased in cycle I of 20.23% to 75. In cycle II the average score of students also increased by 33.18% to 83.08. In the basic score of students' classical completeness learning IPS is 46.15% (not complete). After applied Role Playing learning model on cycle I of student's learning completeness gradually increased to 69.23% (not complete) and on the second cycle student learning completeness classic to 88.46% (thorough). Teacher activity at the first meeting of the first cycle of the percentage is 64.28% with sufficient category. The second meeting increased to 78.57% with good category. At the first meeting of cycle II teacher activity increased to 85.71% with very good category. At the second meeting it increased to 92.85% with very good category. Student activity at first meeting of cycle I the percentage is 60,71% with enough category. the second meeting increased to 78.57% with good category. At the first meeting of the second cycle of student activity increased to 82.14% with good category. At the second meeting increased to 89.28% with very good category.From this research can be concluded that by applying Role Playing learning model can improve student learning outcomes IPS class IIIA SDN 110 Pekanbaru.Keywords: Role Playing, learning achievement social